2022
DOI: 10.1111/jfb.15016
|View full text |Cite
|
Sign up to set email alerts
|

Cause of increased size of acipenseriform eggs infected with Polypodium hydriforme

Abstract: Eggs of acipenseriform fish infected with the parasite Polypodium hydriforme become enlarged during later stages of development. This study examined if the increase in size is due to the increase in nutrients or water in the infected eggs and if the polypodium eggs affect the nutrient levels of the neighbouring eggs in the ovary. Infected and uninfected eggs were collected from parasitized Paddlefish, Polyodon spathula, hosts and unparasitized individuals. Levels of water, protein, carbohydrates, lipids and am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…The parasite was also reported by Hoffman et al (1974) [53] on the eggs of Acipenser fulvescens in the USA, as well as by Okamura et al (2020) [54] and Judd et al (2022) [56]. Dick et al (1991) [55] identified the parasite on Acipenser fulvescens eggs in Canada.…”
Section: Hirudinea and Polypodiozoamentioning
confidence: 64%
“…The parasite was also reported by Hoffman et al (1974) [53] on the eggs of Acipenser fulvescens in the USA, as well as by Okamura et al (2020) [54] and Judd et al (2022) [56]. Dick et al (1991) [55] identified the parasite on Acipenser fulvescens eggs in Canada.…”
Section: Hirudinea and Polypodiozoamentioning
confidence: 64%